Minimization of Energy Consumption Through Improving Purity of Hydrogen By-Product and Adding Heat Exchanger on Acetaldehyde Production Process - Fawwaz, Abdurrahman; Nugraha, Akbar Putra Ajie; Al Rasyid, Muhammad Putra; Muhammad, Refah Hakam (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Improving energy efficiency in the acetaldehyde production process is one of the strategic steps to optimize operations and support the sustainability of the chemical industry. This study aims to analyze the impact of adding a heat exchanger and increasing the mass rate of the feed absorber (water) on energy efficiency and hydrogen purity, as a by-product. Simulations were conducted with thermodynamic modeling-based software to compare the unmodified process system with the modified system. The addition of a heat exchanger was designed to minimize heat energy loss in the system by recycling heat energy from the process stream. Meanwhile, increasing the mass rate of the feed absorber aims to increase the capacity of the water absorber in separating impurity compounds, thereby producing hydrogen with higher purity. Simulation results show that the system modified with the heat exchanger successfully reduces the total energy demand by 1,695,040.81 kJ/h. In addition, increasing the mass rate of the absorber feed significantly improves the hydrogen purity to reach a more optimal level for advanced applications. In conclusion, the combination of adding a heat exchanger and adjusting the mass rate of the feed absorber not only improves energy efficiency, but also provides added value in the form of hydrogen with higher purity. This study provides practical guidance for the development of a more efficient and environmentally friendly acetaldehyde production technology. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).